Frying Time on the Nutritional Content of Strawberry Chips as an Alternative Healthy Snack for Teenagers - Mia Srimiati; Alfisa Ratu Maharani; Annisa Dinya Zahra; Febry Harsanti; Putri Habibah (Sarana Ilmu Indonesia (salnesia), 2023)
Covid-19 is a disease that is transmitted through a virus that attacks the human respiratory system and appeared in early 2020. During the Covid-19 pandemic, people, especially teenagers, were required to increase their immune systems. This study aimed to determine the effect of frying time on the quality of strawberry chips as a healthy snack during the COVID-19 pandemic. The design used was a basic Completely Randomized Design (CRD), by analyzing the results of the organoleptic test using the Kruskal-Wallis test followed by the Mann-Whitney test. The content analysis was selected from the highest treatment value, namely P3 with 4,62 percent water content, 1,73 percent ash, 1,52 percent protein, 17,88 percent fat, 14,44 percent carbohydrates, 8,34 percent fiber, and vitamins C 62,8 mg/100g. The calorie contribution of selected strawberry chips per 40 grams was 223 kcal. In conclusion, the frying time has an effect on the quality of the strawberry chips which has a big effect on the organoleptic characteristics and vitamin C.